El Negligente Deber Objetivo del cuidado de quien ejerce la tutoría del niño, niña. - Rueda Maza., Estefania Thalia (2023)
This Curricular Integration Project focuses on analyzing the care provided by those who exercise child tutorship to children engaged in begging and child labor on the streets, putting the physical integrity of the young people at risk. From my perspective, it would be appropriate to impose a criminal penalty on the guardians of such children found on the streets since they endanger the health and personal development ofthese young people. This research allowed me to examine child begging and child labor, revealing a considerable incidence of these factors and the negative influence they have. Engaging in these activities affects the child's ability to lead a normal life, violates their rights to a dignified life, integral development, and the best interest ofthe child. The Curricular Integration Project employed various methods such as analytical, deductive, inductive, synthetic, exegetic, statistical, and comparative approaches. It also utilized tools such as surveys and interviews, which served as the base for this work. The importance of incorporating criminal measures for guardians who allow or force children to engage in risky activities was determined. Additionally, the high rate of child begging and child labor was identified among other findings. Thus, the project achieved a successful outcome that can help address the issues presented in this Curricular Integration Project.